Focused ultrasound in modern medicine: bioengineering interfaces, molecular effects, and clinical breakthroughs - Li, Xia; Liu, Yi (Frontiers in Bioengineering and Biotechnology, 2025)
Ultrasound technology, first utilized in 1947–1948 for diagnostic applications in obstetrics and gynecology, has significantly expanded its scope to include both diagnostic and therapeutic uses in modern medicine. The advent of continuous therapeutic ultrasound has allowed for its application in treating musculoskeletal pathologies, enhancing fracture healing, and even facilitating tumor treatment when paired with MRI. Ultrasonic cavitation, gas body activation, and mechanical stress are primary non-thermal mechanisms responsible for its biological effects. Recent advancements have expanded ultrasound’s potential to enhance drug delivery, as seen in the sonoporation phenomenon, where ultrasound triggers cell membrane permeability. This process can be reversible or irreversible, offering exciting possibilities for targeted treatments. Additionally, microbubbles are used to intensify US-induced effects, contributing to therapeutic applications such as high-intensity focused ultrasound (HIFU) for cancer ablation and drug delivery. Molecular ultrasound imaging, which incorporates microbubbles targeted to specific biomarkers, allows for the non-invasive visualization of molecular processes such as angiogenesis, inflammation, and thrombosis. This capability holds significant promise for early disease detection and monitoring, particularly in cancer and cardiovascular conditions. The aim of this review is to explore the diverse molecular mechanisms underlying ultrasound’s therapeutic and diagnostic capabilities, assess its potential for improving patient outcomes, and highlight the future directions for clinical integration of ultrasound in medicine.